Modern possibilities of MRI-based diagnosis of multiple sclerosis. Literature review - I. Yu. Degtyarev; V. D. Zavadovskaya; A. P. Kurazhov; M. A. Zorkaltsev; V. M. Alifirova; K. S. Sukhanova (Бюллетень сибирской медицины)
Multiple sclerosis remains the most common demyelinating disease of the central nervous system and ranks first among neurological diseases that lead to disability in young people. The most important diagnostic and prognostic marker, especially at an early stage of the disease, is magnetic resonance imaging (MRI), which currently remains the only method that allows to explore the entire central nervous system in vivo.The review presents literature data on modern achievements in MRI-based diagnosis of multiple sclerosis. Key attention is paid to such promising methods as assessment of brain and spinal cord atrophy, brain perfusion MRI, and diffusion tensor imaging. Implementation of these approaches in MRI can help solve the problem of early diagnosis of multiple sclerosis and determine more reliable markers of a response to ongoing therapy.